(untitled) (Sirte Journal of Medical Sciences, 2023)
Background: Eye diseases in children are important cause of medical consultation. This study aimed to determine the distribution and spectrum of childhood eye diseases at the pediatric outpatient clinics of Makkah eye hospital in Aden. Materials and method:This is an observational retrospective study. The medical records of all patients aged 16 years or younger who were seen at the pediatric ophthalmology outpatient clinics during the year 2021, were reviewed. The following data were recorded for each patient: sex, age, residency, site of trauma, site of disease, and diagnosis. Descriptive statistics were computed for continuous and categorical variables. The statistics computed included mean and standard deviations (SD) of continuous variables and are presented as mean ± SD, frequencies and percentages of categorical factors. Results: Total study patients were 146 (males were 61.6% and females were 38.4%). Most of them 58.2% were from rural areas. Their age ranged between 1 month to 16 years and their mean age was 7.1 ± 4.1 years. Children aged ≤ 5 years were (37.7%), of the age group 6 – 10 years were (35.6%) and of the age group 11 and 16 years were (26.7%). The most common eye disorders were ocular trauma in (43.2%) children. Squint was the second commonest disease and accounted (14.4%). Congenital glaucoma found in (11.6%) children, refractive error found in (9.6%) patients, and congenital cataract in (6.9%) children. Ocular trauma was predominant (19.9%) in the age group 6-10 years, while squint was predominant (6.8%) in the age group 10-16 years old and congenital glaucoma was predominant (10.2%) in the age group ≤ 5years. The highest frequency of refractive errors were found in children aged between 6 to 10 years and children aged between 11 to 16 years, (P = 0.000). Conclusion: The most common eye diseases in our study were ocular injuries, squint, congenital glaucoma, refractive errors and congenital cataract, respectively.